2018
DOI: 10.1111/cea.13173
|View full text |Cite
|
Sign up to set email alerts
|

Sputum‐to‐serum hydrogen sulphide ratio as a novel biomarker of predicting future risks of asthma exacerbation

Abstract: The H S ratio may provide useful information on predicting future risks of asthma exacerbation, as well as on obstructive neutrophilic airway inflammation as one of the non-Th2 biomarkers, in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In this study of asthmatics of varying severity, healthy subjects' serum and sputum H 2 S have been examined. 57 Serum levels were lower and sputum levels higher in those with frequent exacerbations compared to those with fewer and elevated sputum H 2 S predicted future exacerbations. Thus, a higher ratio of sputum to serum H 2 S seems to predict more exacerbations though it is entirely unclear why H 2 S should behave in this way.…”
Section: Predicting Future Asthma Attacksmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study of asthmatics of varying severity, healthy subjects' serum and sputum H 2 S have been examined. 57 Serum levels were lower and sputum levels higher in those with frequent exacerbations compared to those with fewer and elevated sputum H 2 S predicted future exacerbations. Thus, a higher ratio of sputum to serum H 2 S seems to predict more exacerbations though it is entirely unclear why H 2 S should behave in this way.…”
Section: Predicting Future Asthma Attacksmentioning
confidence: 90%
“…H 2 S has recently been shown to be an important gaseous signalling molecule involved in modulating airway and vascular smooth muscle. In this study of asthmatics of varying severity, healthy subjects' serum and sputum H 2 S have been examined . Serum levels were lower and sputum levels higher in those with frequent exacerbations compared to those with fewer and elevated sputum H 2 S predicted future exacerbations.…”
Section: Asthma and Rhinitismentioning
confidence: 99%
“…There can be some possible reasons for this discrepancy including different methods used for H 2 S assay and various factors which can influence the H 2 S level, such as exacerbation of disease and degree of inflammation. In parallel, the level of H 2 S in asthmatic patients measured in the sputum was clearly elevated compared with healthy donors: 26–27 μM vs.11.4 μM [ 138 , 140 ] and 31.9 μM vs 19.7 μM [ 141 , 142 ], ( Table 2 ). It seems that sputum H 2 S particularly correlates with the degree of airflow limitation and it has been suggested that H 2 S has potential as a novel biomarker for COPD and asthma [ 140 ].…”
Section: Reactive Sulfur Species In Diseasesmentioning
confidence: 93%
“…Macrophages from sputum samples of asthma patients express reduced levels of Gal-1 and Gal-9 (82). Several human studies have shown a decrease in serum or exhaled-breath H 2 S levels in both adult and infants (220222). Moreover, lower H 2 S levels are correlated with abnormal pulmonary lung function tests and severity of asthma (220, 221).…”
Section: Impaired Resolution Of Chronic Inflammation In the Intestinementioning
confidence: 99%